On the Optical Properties of the Cu2ZnSn[S1−xSex]4 System in the IR Range - Dilshod, Nematov; Kholmirzo, Kholmurodov; Aliona, Stanchik; Kahramon, Fayzullaev; Viktoriya, Gnatovskaya; Tamerlan, Kudzoev (Trends in Sciences, 2022)
Following the recent classification by the European Commission of some elements as critical raw materials (CRM), there is an increasing interest in the development of CRM-free thin film photovoltaic (PV) technologies, including kesterite materials. Moreover, starting with the performance breakthrough reported by IBM in 2010, the efficiency of kesterite-based solar cells steadily progressed in the following years achieving. Therefore, in recent years, there has been a significant research effort to develop kesterite-based devices. However, despite the large number of theoretical and experimental works, many aspects of the problem have not yet been fully studied. Therefore, the issues considered in the article, especially the behavior of the absorption and photoconductivity spectra of the Cu2ZnSn[S1−xSex]4 system, depending on the S/Se ratio, are extremely important and, at the same time, one of the topical and poorly studied problems. In this work, using quantum-chemical calculations in the framework of density functional theory (DFT), we study the optical properties of semiconductor nanocrystals of kesterite Cu2ZnSnS4 doped with Se. Using the WIEN2k package, the concentration dependences of the optical characteristics of nanocrystals of the Cu2ZnSn[S1−xSex]4 system (x = 0.00, 0.25, 0.50, 0.75 and 1.00) were calculated. It is shown that doping with Se at the S position leads to a noticeable improvement in the photoabsorbing properties of these nanocrystals, as well as their photoconductivity in the IR range. The calculated absorption and extinction spectra, as well as the refractive indices and permittivity of the materials under study, are compared with experimental data known from the literature. The data obtained will significantly enrich the existing knowledge about the materials under study and will contribute to the expansion of the field of application of these compounds in optoelectronic devices. HIGHLIGHTS With an increase in the Se concentration, the absorbing properties and photoconductivity of the nanocrystals of the Cu2ZnSn[S1−xSex]4 system increase The optical band gap narrows with increasing Se/S ratio Curves k(ω) and α (ω) correspond to the maxima of e2 (w) Pure Cu2ZnSnSe4 has the maximum absorption in the IR range GRAPHICAL ABSTRACT